Le journalisme sous l’emprise de la catastrophe - Marc Lits; Grégoire Lits; Brieuc Lits (Communication)
The authors examine the role media plays in the configuration of history. Based on content analyses of two retrospective and prospective supplements published by the Belgian daily newspaper Le Soir, they highlight a number of exploratory research avenues on the central role of risk and disaster data repositories in the media’s selection of important historic facts. They also show how questions on the central role of science and expertise in our relationship with the world today seem to be a key prism through which to examine the media’s take on the past, present, and future.